Dampak Budaya Jawa terhadap Perilaku Masyarakat Desa Wonosari Kecamatan Pantai Cermin - Indah Lestari (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
Over time, the behavior of the people of Wonosari Village, Pantai Cermin District, is much influenced by the existence of Javanese culture that is used in everyday life by the people of Wonosari Village, Pantai Cermin District. Such as the Slametan event, the upload event, among-among, the rice field event, and other Javanese cultural events. Problem formulation (1). How is non-Javanese ethnic culture assimilated with Javanese culture in Wonosari Village, Pantai Cermin District? (2). How are the slametans, village clean-ups, and rice field events held in Wonosari Village, Pantai Cermin District? (3). How is Javanese culture used as the main tradition in Wonosari Village, Pantai Cermin District?. The objectives of this research are (a). To find out the non-Javanese ethnic culture assimilated with Javanese Culture in Wonosari Village, Pantai Cermin District. (b). To find out the implementation of slametan, village clean-up, and rice field activities in Wonosari Village, Pantai Cermin District. (c). To find out Javanese culture is used as the main tradition in Wonosari Village, Pantai Cermin District. The type of research that will be used is qualitative research with descriptive research. In accordance with the title of the study, the research is located in Wonosari Village, Pantai Cermin District. The data collection methods are Observation/Observation Methods, Interview Methods/Interviews and Documentation. The data analysis techniques used are: Data Reduction, Data Display, Comparative Analysis, and Drawing Conclusions. The results showed that non-Javanese ethnic groups were beginning to be affected by the existence of Javanese ethnic culture, seen from them participating in every event carried out by Javanese ethnic groups related to Javanese culture in order to create good interaction among Wonosari Village residents, until they could use the Javanese language. Javanese culture also affects a good level of kinship because with this culture can create togetherness and friendship between the non-Javanese and the Javanese. The tradition that has been passed down from generation to generation is still carried out well by the Javanese people in the village of Wonosari. Javanese culture in Wonosari Village, Pantai Cermin District, Serdang Bedagai Regency is used as the main tradition because the majority of the village community is Javanese, and non-Javanese people live to follow it, including people who have lived long before the Javanese entered the Wonosari Village.